Combining radiofrequency ablation and ethanol injection may achieve comparable long‐term outcomes in larger hepatocellular carcinoma (3.1–4 cm) and in high‐risk locations. Issue 8 (2nd June 2014) - Lin, Ji‐Wei; Lin, Chen‐Chun; Chen, Wei‐Ting; Lin, Shi‐Ming
Abstract: Radiofrequency ablation (RFA) is more effective for hepatocellular carcinoma (HCC) < 3 cm. Combining percutaneous ethanol injection and RFA for HCC can increase ablation; however, the long‐term outcome remains unknown. The aim of this study was to compare long‐term outcomes between patients with HCC of 2–3 cm versus 3.1–4 cm and in high‐risk versus non‐high‐risk locations after combination therapy. The primary endpoint was overall survival and the secondary endpoint was local tumor progression (LTP). Fifty‐four consecutive patients with 72 tumors were enrolled. Twenty‐two (30.6%) tumors and 60 (83.3%) tumors were of 3.1–4 cm and in high‐risk locations, respectively. Primary technique effectiveness was comparable between HCC of 2–3 cm versus 3.1–4 cm (98% vs. 95.5%, p  = 0.521), and HCC in non‐high risk and high‐risk locations (100% vs. 96.7%, p  = 1.000). The cumulative survival rates at 1 year, 3 years, and 5 years were 90.3%, 78.9%, and 60.3%, respectively, in patients with HCC of 2–3 cm; 95.0%, 84.4%, and 69.3% in HCC of 3.1–4.0 cm ( p  = 0.397); 90.0%, 71.1%, and 71.1% in patients with HCC in non‐high‐risk locations; and 92.7%, 81.6%, and 65.4% in high‐risk locations ( p  = 0.979). The cumulative LTP rates at 1 year, 3 years, and 5 years were 10.2%, 32.6%, and 32.6%, respectively, in all HCCs; 12.6%, 33.9%, and 33.9% in HCC of 2–3 cm; 4.8%, 29.5%, and 29.5% in HCC of 3.1–4 cm ( p  = 0.616); 16.7%, 50.0%, and 50.0% in patients with HCC in non‐high‐risk locations; and 8.8%, 29.9%, and 29.9% in patients with HCC in high‐risk locations ( p  = 0.283). The cumulative survival and LTP rates were not significantly different among the various subgroups. Combining RFA and percutaneous ethanol injection achieved comparable long‐term outcomes in HCCs of 2–3 cm versus 3.1–4.0 cm and in high‐risk versus non‐high‐risk locations. A randomized controlled or cohort studies with larger sample size are warranted.